Prognostic Impact of Direct 131I Therapy After Detection of Biochemical Recurrence in Intermediate or High-Risk Differentiated Thyroid Cancer: A Retrospective Cohort Study - Carrillo, José F.; Vázquez-Romo, Rafael; Ramírez-Ortega, Margarita C.; Carrillo, Liliana C.; Gómez-Argumosa, Edgar; Oñate-Ocaña, Luis F. (Frontiers in Endocrinology, 2019)
Background: Patients treated for intermediate- or high-risk differentiated thyroid carcinoma (DTC) and Thyroglobulin (TG) elevation during follow-up, require a diagnostic whole-body scan (DWBS) and if positive, 131I treatment. This approach can lead to a delay in treatment and increased costs. The purpose of this study is to compare the oncologic outcomes associated to DWBS results in patients with DTC and a first biochemical recurrence. Methods: Retrospective cohort study of patients with intermediate- or high-risk DTC treated with total thyroidectomy, 131I ablation and who developed TG elevation during follow-up, between January 2007 and December 2015. Cohort A included patients who underwent a DWBS with 5 mCi of 131I prior to the therapeutic dosage, and cohort B included those who only received a therapeutic dosage of 131I, without a DWBS. Main outcomes were second recurrence (SR) and disease-free survival (DFS). The diagnostic accuracy of DWBS was analyzed. Results: Cohorts A and B had 74 and 41 patients, each. By multivariate analysis, age, differentiation grade, TN classification, ablation dose, and DWBS result (odds ratio 55.1; 95% CI 11.3-269) were associated with SR (p<0.0001); age, male gender, ablation dose and DWBS result (hazard ratio 7.79; 95% CI 3.67-16.5) were independent factors associated with DFS (p<0.0001). DWBS diagnostic accuracy was 36.48%. Conclusion: 131I treatment in patients with DTC biochemical recurrence and no DWBS is associated with a significantly lower frequency of SR and an increased DFS. The diagnostic accuracy of DWBS is low, and its clinical efficiency should be defined in prospective phase III studies.